Cognitive spare capacity: evaluation data and its association with comprehension of dynamic conversations - Keidser, Gitte; Best, Virginia; Freeston, Katrina; Boyce, Alexandra (Frontiers in Psychology, 2015)
It is well established that communication involves the working memory system, which becomes increasingly engaged in understanding speech as the input signal degrades. The more resources allocated to recovering a degraded input signal, the fewer resources, referred to as cognitive spare capacity, remain for higher-level processing of speech. Using simulated natural listening environments, the aims of this paper were to (1) evaluate an English version of a recently introduced auditory test to measure cognitive spare capacity that targets the updating process of the executive function, (2) investigate if the test predicts speech comprehension better than the reading span test commonly used to measure working memory capacity, and (3) determine if the test is sensitive to increasing the number of attended locations during listening. In experiment I, the cognitive spare capacity test was presented using a male and a female talker, in quiet and in spatially separated babble- and cafeteria-noises, in an audio-only and in an audio-visual mode. Data collected on 21 listeners with normal and impaired hearing confirmed that the English version of the cognitive spare capacity test is sensitive to population group, noise condition, and clarity of speech, but not presentation modality. In experiment II, performance by 27 normal-hearing listeners on a novel speech comprehension test presented in noise was significantly associated with working memory capacity, but not with cognitive spare capacity. Moreover, this group showed no significant difference in cognitive spare capacity as the number of talker locations in the test increased. There was no consistent association between the cognitive spare capacity test and the reading span test. It is recommended that future studies investigate the psychometric properties of the cognitive spare capacity test, and examine its sensitivity to the complexity of the listening environment in participants with both normal and impaired hearing.